Biathlon elite`s competitive performance versus physical fitness analysis - Adodin, N. V.; Myakinchenko, E. B.; Zakharov, G. G.; Beleva, A. N. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to rate and analyze the physical fitness variance versus the competitive success data in the national biathlon elite. Methods and structure of the study. We used in the study the test data flow produced by the regular staged combined tests of the 27+1.4 year-old healthy uninjured elite biathletes (n=6) qualified for the Russian national team, active in trainings and competitions and subject to the staged combined tests at least six times for the study period. We rated their competitive performance in 18 sprint events at the 2018-19/ 2019-20 World Cups and World Championships using the data available at https://biathlonresults.com/ and using the competitive performance rating method described earlier [3]. The staged combined tests were designed to process the strength, alactate/ aerobic muscle power and cardio-respiratory system functions test data generated by the ski ergometer and treadmill tests with modern standard equipment [2, 5]. The test data were statistically processed and analyzed by Statistica 10.0 software toolkit using nonparametric Mann-Whitney test, with the correlations rated by the Spearman test with the difference significance threshold of 0.05. Based on the competitive performance and Rp data analysis for the last two seasons, we split up the sample into two groups (G1, G2) of three people each. Results and Conclusion. The study data and analyses found the biathletes with better average competitive success rates for the period being more stable in the seasonal competitive performance. The group with the lower competitive success and competitive stability rates was tested with a higher variance of the cardio-respiratory system, energy efficiency and muscle aerobic power test rates in the precompetitive periods. On the whole, the competitive stability (St) rates were found significantly correlated with the physical fitness variances, albeit the positive and negative correlations were virtually equal. This is the reason for us to assume that correlations of the individual competitive performance with adaptabilities in the elite biathletes' training systems deserve further special studies in the context of the training service improvement initiatives.